Trends and climate response in the yield of staple crops across Northeast China - Xiao, Dengpan; Yang, Xiaohui; Bai, Huizi; Tang, Jianzhao; Tao, Fulu (Frontiers in Sustainable Food Systems, 2024)
Understanding how climate change has been affecting crop yield is a prerequisite to inform adaptation decisions and to ensure global food security. The Northeast China (NEC), located in high-latitude area, is significantly affected by climate change. There is a high demand for quantitative information on impacts of climate variability on crop yields in NEC. In this study, we applied panel regression models to explore the yield-climate relationship and its spatial variations based on experimentally observed yield (Ys) and the county-scale statistical yield (Yc) of three typical crops (e.g., maize, rice and soybean) across NEC from 1981 to 2010, as well as contemporary climate data. The results indicated that Ys (Yc) of maize, rice and soybean during the past three decades increased by 64.2% (82.0%), 47.5% (55.3%), and 59.2% (58.0%), respectively. Moreover, we found climate during crop growth period had changed significantly and the change had caused measurable impacts on crop yields. Changes in temperature, precipitation and solar radiation jointly decreased Ys (Yc) of maize and soybean by 1.3% (0.7%) and 0.3% (1.1%), respectively, however increased Ys (Yc) of rice by 1.2% (2.2%), with a large spatial difference. Therefore, the impact of climate change on yields of three crops was far less than the actual increase in crop yields. Our finding suggest that other factors, mainly improved management practices, may be the main reason for the significant increase in crop yields in NEC over the past few decades. Although historical climate change also played an important role in the yields of three crops, certain improvement in management measures not only compensated for the negative impact of climate change, but also greatly promoted the increase in crop yields. Therefore, in proposing strategies for crop production to cope with climate change, we need in-depth assessments of the role of improved management.